Simulacra dalam Industri Hiburan Visual; Studi kasus Ragnarok Online - Alvanov Zpalanzani Mansoor; Yasraf Amir Piliang (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2010)
Comic is one of media that emphasize its content delivery through visual sequence. It attracts many researchers because this media is a plane based media (2D) instead of most media which delivers its content in time based media. In designing a story based on visual sequence, there are framing, imaging, wayfinding acitivities in forming a complex visual storytelling especially in comics. Especially in Japan, the development of framing, imaging, and methods of designing a sequence which makes the reader easily read the story through panels in comics are well developed and shared from comic artists toward their assistants. This method is known as graphic narrative and visual storytelling and applied not only on comics but almost on all visual entertainment media and influence each other then creates cycle of media. The cycle of media surfaces simulacra and unique hypereality phenomenon. This paper tries to depict the uniqueness of simulacra of media cycle phenomenon on Ragnarok Online case study in Indonesia which will enrich the study of visual culture.